2021
DOI: 10.1002/jbm4.10520
|View full text |Cite
|
Sign up to set email alerts
|

Brd4 Inactivation Increases Adenoviral Delivery of BMP2 for Paracrine Stimulation of Osteogenic Differentiation as a Gene Therapeutic Concept to Enhance Bone Healing

Abstract: Bromodomain (BRD) proteins are histone code interpreters that recognize acetylated lysines and link the dynamic state of chromatin with the transcriptional machinery. Here, we demonstrate that ablation of the Brd4 gene in primary mouse bone marrow-derived mesenchymal stem cells via a conditional Brd4 fl/fl allele suppresses osteogenic lineage commitment. Remarkably, loss of Brd4 function also enhances expression of genes in engineered adenoviral vectors, including Cre recombinase and green fluorescent protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Because we previously showed that BRD4 is required for osteogenic and chondrogenic differentiation and skeletal formation, [37][38][39] we sought to determine whether the effects of BET inhibition (i.e., JQ1) on myofibroblast differentiation can be mirrored by BRD4 depletion (Figure 5A). Robust siRNAmediated BRD4 depletion is confirmed by RT-qPCR (Figure 5B) and western blot analysis (Figure 6, Supporting Information: Figure 2B) 4 days after transfection in all three primary cell lines.…”
Section: Robust Depletion Of Brd4 Expression In Primary Knee Outgrowt...mentioning
confidence: 99%
See 3 more Smart Citations
“…Because we previously showed that BRD4 is required for osteogenic and chondrogenic differentiation and skeletal formation, [37][38][39] we sought to determine whether the effects of BET inhibition (i.e., JQ1) on myofibroblast differentiation can be mirrored by BRD4 depletion (Figure 5A). Robust siRNAmediated BRD4 depletion is confirmed by RT-qPCR (Figure 5B) and western blot analysis (Figure 6, Supporting Information: Figure 2B) 4 days after transfection in all three primary cell lines.…”
Section: Robust Depletion Of Brd4 Expression In Primary Knee Outgrowt...mentioning
confidence: 99%
“…While BET-targeting agents such as JQ1 alter activities of several BET proteins, our present target validation focused on BRD4 as our recent studies revealed a unique role for this protein in mesenchymal lineage differentiation and skeletal formation. [37][38][39] Although BRD2 mRNA levels are higher in preosteoblasts, BRD4 depletion was more robust at inhibiting osteogenic commitment when compared to BRD2 depletion, 38 suggesting that BRD4 is a critical epigenetic regulator of lineage allocation of mesenchymal progenitors. The contribution of BRD4 on the differentiation of mesenchymal progenitors is further supporter by studies showing the allocation of BRD4 to lineage-specific genes after the administration of differentiation stimuli.…”
Section: Brd4 Knock-down Suppresses Collagen Expression and Depositionmentioning
confidence: 99%
See 2 more Smart Citations